KAJIAN EFEKTIVITAS PEMBELAJARAN DARING MENGGUNAKAN GOOGLE CLASSROOM PADA MATA PELAJARAN KIMIA - Firda Kisdamayanti; Pangoloan Soleman Ritonga (Journal of Chemistry Education and Integration, 2023)
AbstractThe background of this research was the presence of the covid-19 virus which is spreading rapidly throughout Indonesia, the number of people infected has made the government dismiss students, teachers, college students, lecturers, and workers. One of the activities that are obstracted due to this pandemic is the learning process. Therefore, the government has established an online teaching and learning system policy to stop the spread of covid-19. This alternative makes google classroom one of the media that can be used to assist teachers and students in carrying out online teaching and learning activities. The aim of this research was to know the effectiveness of online learning through Google Classroom on Chemistry Subject at State Senior High School 2 Singingi. The technique of collecting data in this research was online survey method with google form. The sample of this research was XI MIA 1 class that is consisted of 30 students based on purposive sampling technique. The questionnaire instrument in this research used the QAIT model indicators according to Slavin. Based on the research findings, the mean percentages of each effectiveness indicator showed that the online learning that is carried out is enough to replace face to face learning during the pandemic, the students also feel that the goals of online learning activities can be achieved well using Google classroom as a media. In addition, supporting data in the form of daily test results showed that the percentage of complete learning is 96,66% of students can achieve the standard of minimum criteria of mastery learning (KKM). Then, there is the effectiveness of online learning through google classroom on chemistry subject at state senior high school 2 Singingi. Keywords: Learning Effectiveness, Google Classroom, Colloid, Online Learning